A Two-Tier Post-Processing Framework for Lightweight Video Anomaly Detection - Akhtar, Muhammad Hannan (2025)
A Master of Science thesis in Computer Engineering by Muhammad Hannan Akhtar entitled, “A Two-Tier Post-Processing Framework for Lightweight Video Anomaly Detection”, submitted in November 2025. Thesis advisor is Dr. Tamer Shanableh. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).